Street Lighting Design with IoT-Based Energy Management in Cibuluh Village - Sarosa Castrena Abadi; Danu Jaya Saputro; Muhammad Nursyam Rizal; Anggraeni Mulyadewi; Ega Mardoyo (Brilliance: Research of Artificial Intelligence, 2026)
This study presented the design and implementation of an Internet of Things–based public street lighting system with energy management in Cibuluh Village, Tanjung Siang District, Subang Regency. The project aimed to improve lighting reliability in areas with limited grid access while reducing energy consumption and operational costs. The system employed solar panels as the primary energy source, battery storage, and light-emitting diode lamps equipped with smart dimming features. This approach enhances system autonomy, minimizes maintenance requirements, increases operational efficiency, ensures consistent illumination quality, and provides a scalable model suitable for broader rural infrastructure deployment nationwide. Energy management was achieved through the integration of light-dependent resistor and passive infrared sensors to adapt lamp brightness based on environmental light conditions and road activity. Electrical parameters, including voltage, current, and power, were monitored using a direct current power measurement module and transmitted via long-range wireless communication to a centralized database. Data visualization was provided through a real-time monitoring dashboard. The system was developed using the ADDIE research and development model and was implemented directly in the village environment. Evaluation results showed stable electrical performance, effective energy savings, reliable data transmission in hilly areas, and improved sustainability of street lighting operations. The proposed system demonstrated its suitability as an efficient and autonomous public lighting solution for rural areas.